The Effect of Levothyroxine on Expression of Inflammation-Related Genes in Healthy Subjects: A Controlled Randomized Crossover Study - Stuijver, D. J. F.; Elbers, L. P. B.; van Zaane, B.; Dekkers, O. M.; Spek, C. A.; Gerdes, V. E. A.; Reitsma, P. H.; Brandjes, D. P. M. (Hormone and Metabolic Research, 2014)
An excess of thyroid hormone leads to a prothrombotic state; however, the underlying pathophysiological mechanisms remain unknown. As evidence points towards an extensive “cross-talk” between the inflammatory and coagulation cascade, inflammation has been claimed as a possible mechanism through which different risk factors trigger venous thrombus formation. We aimed to study changes in expression of inflammation-related genes of the leukocyte RNA expression profile in healthy subjects in response to supraphysiological doses of levothyroxine. In a randomized single-blinded crossover design, 12 healthy volunteers (aged 18–40 years) received levothyroxine and no medication, both for 14 days with a wash-out period of at least 28 days between the periods. Blood was sampled at baseline and day 14 of each study period. MRNA was isolated from whole blood and used for multiplex ligation-dependent probe amplification to study the expression of inflammation-related genes. Compared to the control situation no significant changes were found in the expression of proinflammatory cytokines and mediators after the intake of levothyroxine. The results of this study show that high thyroid hormone levels do not lead to an altered inflammatory profile. This provides evidence against a major role of the inflammatory system as mediator in the effect of thyroid hormone on the coagulation system. The mechanisms by which thyroid hormone may influence coagulation proteins remain to be elucidated.
Keywords: hyperthyroidism; inflammation; coagulation; venous thrombosis